THE DIFFICULT ART OF BEING AN INDIGENOUS TEACHER: TEACHING MATHEMATICS IN THE EARLY YEARS OF ELEMENTARY SCHOOL - Cristiane do Socorro dos Santos Nery; Iran Abreu Mendes (Universidade do Estado do Rio de Janeiro (UERJ), 2023)
Indigenous art in its different forms of representation, such as painting, music, dance, and crafts, expresses sociocultural processes of production, refinement, and updating of knowledge, which is passed from generation to generation. These processes involve a way of communicating, teaching, and learning that is unique to indigenous societies. Being an indigenous teacher today requires mobilizing the knowledge of tradition and school knowledge, aiming at the development of curricula and methodologies in line with the community's reality. It is with this principle that I begin the discussion in this article, which aims to identify the challenges and advances in the teaching of mathematics, based on the curriculum and on the ethnographic reports of indigenous teachers from the early grades of elementary school. The difficulties in teaching mathematics in indigenous schools in Amapá are discussed, based on a documental study and semi-structured interviews with indigenous teachers. In the theoretical framework the concepts of knowledge of tradition and curriculum come into play. The results revealed that the teaching of mathematics in indigenous school education is a challenge to be faced by indigenous teachers, the community, the leaders, and the militant (non-indigenous) teachers, in view of the effectiveness of a school curriculum that dialogues with the knowledge of tradition. Finally, we indicate the importance of new studies that discuss the curriculum, the teaching methodologies, and the dialogue with the knowledge of tradition in the indigenous context.